Refractory coeliac sprue is a diffuse gastrointestinal disease. Issue 2 (1st February 2003) - Verkarre, V; Asnafi, V; Lecomte, T; Mariaud-De Serre, N Patey; Leborgne, M; Grosdidier, E; Le Bihan, C; Macintyre, E; Cellier, C; Cerf-Bensussan, N; Brousse, N
Abstract : Background: Refractory coeliac sprue (RCS) with an immunophenotypically aberrant clonal intraepithelial lymphocyte (IEL) population is considered a cryptic form of intestinal T cell lymphoma. Aims: To investigate the distribution of the abnormal and monoclonal IEL population in the digestive tract of RCS patients. Patients and methods: We compared the frequency of lymphocytic gastritis (LG) and lymphocytic colitis (LC), together with IEL phenotype and T cell clonality, in gastric and colonic samples from 15 adults with RCS (all with aberrant CD3 intracytoplasmic + surface − CD8 − clonal IELs on duodenojejunal biopsies), 18 patients with active coeliac disease (ACD), and 10 patients with coeliac disease (CD) on a gluten free diet (GFD-CD) by means of immunohistochemistry and multiplex polymerase chain reaction amplification of the T cell receptor γ gene (TCR-γ) rearrangement. Blood samples of nine RCS patients were also tested for clonality. Results: LG was found in 9/14 (64%), 11/18 (61%), and 3/10 (30%) patients with RCS, ACD, and GFD-CD, respectively, while LC was found in 6/11 (55%), 3/4 (75%), and 2/3 (66%) patients. Contrary to CD, all samples from patients with LG and LC showed an aberrant IEL phenotype. Monoclonal TCR-γ rearrangements were detected in 8/13 (62%), 8/10 (80%), and 4/9 (44%) of gastric, colonic, and blood samples, respectively, from RCS patients, while in CD patients such rearrangements were only found in 2/25 (8%) gastric samples. Conclusion: The immunophenotypically aberrant monoclonal IEL population present in the small intestine of patients with RCS frequently disseminates to the blood and the entire gastrointestinal epithelium, suggesting that this is a diffuse gastrointestinal disease.